Komunikasi, Karang Taruna, Manaj Penguatan Komunikasi Karang Taruna Melalui Pelatihan Manajemen Organisasi di Dusun Daleman, Desa Jetis - Dzumirrotin, Shofiya; Iqabakti, Jihad; Istiqomah, Afifah Nur; Rokhmah, Nisma Ismatur; Nadia, Anis; Solikah, Cantika Intan; Wahid, Kholil Nur; Syabana, Anindya Zalfa; Muna, Farah Linailil; Meysa Putri, Maura Syelin; Rohman, Hafid Nur Abdul; Mulyani, Diah Suci; Kibtiyah, Mariah (Universitas Islam Internasional Darullughah Wadda'wah, 2025)
The problem of weak communication between members is a major challenge in the Karang Taruna organization of the Ikatan Bina Karya Remaja of Daleman Hamlet. The focus of this service is to strengthen organizational capacity through training in organizational management and communication. The purpose of this activity is to increase the effectiveness of the Youth Organization's role as a forum for youth empowerment. The method used is Participatory Action Research (PAR) with participatory observation techniques, in-depth interviews, and documentation. The implementation strategy includes problem identification, action planning, training implementation, and evaluation and reflection. The results showed an increase in the managerial skills of the board, the formation of an effective communication system between members, and strengthening collaboration in empowerment programs. This training proves that strengthening organizational capacity through a participatory approach can create positive and sustainable changes in the structure and dynamics of Youth Organization.